Moderation of Religion in the Identity of the Sasak Community: Islamic Education Perspective - Baiq Mulianah (Schemata: Jurnal Pascasarjana UIN Mataram, 2024)
This article examines the role of Islamic education in strengthening religious moderation within the Sasak community. The research background illustrates how moderation values are reflected in Sasak cultural identity amidst contemporary social and religious dynamics. The research aims to identify the contribution of Islamic education in enhancing religious moderation, preserving cultural identity, and addressing complex challenges of globalization. The theoretical framework engages concepts of moderation values within the context of Sasak education and culture. The research adopts a descriptive-analytical method with a qualitative approach, employing case studies and literature analysis. Findings indicate that Islamic education plays a crucial role in shaping religiously moderate characters among the Sasak community, reinforcing their identity, and providing a foundation to uphold traditional values amidst global currents. In conclusion, Islamic education serves not only as a religious tool but also as a guardian of cultural values in a modern context.   Artikel ini meneliti peran pendidikan Islam dalam memperkuat karakter moderasi beragama di kalangan masyarakat Sasak. Latar belakang penelitian menggambarkan bagaimana nilai-nilai moderasi tercermin dalam identitas budaya Sasak di tengah dinamika sosial dan religius kontemporer. Tujuan penelitian adalah untuk mengidentifikasi kontribusi pendidikan Islam dalam memperkuat moderasi beragama, mempertahankan identitas budaya, dan mengatasi tantangan globalisasi yang kompleks. Kerangka pemikiran melibatkan konsep-konsep tentang nilai-nilai moderasi dalam konteks pendidikan dan budaya Sasak. Pendekatan penelitian menggunakan metode deskriptif-analitis dengan pendekatan kualitatif, melalui studi kasus dan analisis literatur. Temuan penelitian menunjukkan bahwa pendidikan Islam memainkan peran penting dalam pembentukan karakter moderasi beragama di kalangan masyarakat Sasak, memperkuat identitas mereka, dan memberikan landasan untuk menjaga nilai-nilai tradisional dalam menghadapi arus globalisasi. Simpulannya, pendidikan Islam tidak hanya sebagai instrumen keagamaan, tetapi juga sebagai penjaga nilai-nilai budaya dalam konteks modern.